Kesediaan, Penerimaan Dan Pengoperasian Guru Reka Bentuk dan Teknologi Terhadap Amalan dalam Pentaksiran Berasaskan Sekolah (Sains Humanika, 2018)
This study aims to identify the readiness, acceptance and operation of Design and Technology teachers on Practice in School-Based Assessment (PBS). PBS is a holistic assessment that assesses cognitive (intellectual), affective (emotional and spiritual) aspects and psychomotor (physical) in line with the National Education Standard and Primary School Curriculum (KSSR) Philosophy. This study aims to examine the implementation of PS practices on Design and Technology teachers in national schools in the southern states of Negeri Sembilan, Melaka and Johor. Elements to be studied are the level of teacher practice in the implementation of PS. The sampling type used was a simple random sampling where the sample of the study was 275 teachers consisting of teachers who taught Year 4, 5 and 6 of the 275 selected schools. The research instrument used was a questionnaire distributed to respondents. A total of 12 questionnaire items have been developed and have gone through the validity and reliability process. Teachers practice before, during and after the assessment is good at min 3.9673, 4.0029 and 4.0218 respectively. Data collected were analyzed using Statistical Packages For Social Science (SPSS) software. Overall, the findings show that the practice of teachers in implementing the School Assessment is at a good level with the overall mean of 4.0048 and the standard deviation of .57239. Hopefully, the results of this study will help to better teachers in implementing the School Assessment.
Keywords: Teacher practice; school based assessment; design and technology